(3LGeY GdeSGfjO hGdSff GdgGOj dCbhe Sffs - (3ESeGYjd Hf YeQ Hf cKjQ Hf Vqh Hf OQY GdbQTj GdHUQhj Ke GdOeTbqj, CHh GdaOGA, YeGO GdOjf,J (B774 (3g` s
(3ChdgG (B:s
(3jHJOF HLYaQ Hf YjGV GdeOfj s
(3BNQgG (B:s
(3hjfJgj HBNQ eSfO CHj gQjQI s
(3GdfSNI HgG MhGTs
(3LRA BNQ efgs
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B320 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B2 - (3U (B283s
Keywords: (3GdMOjK h GdeUWdMs